Perlindungan Korban Human Trafficking Perspektif Hukum Pidana dan Hak Asasi Manusia - Asnawi, Habib Shulton; Nawawi, M Anwar; Setiawan, Agus; Mu'in, Fathul (MORALITY: Jurnal Ilmu Hukum, 2022)
Abstract Efforts to protect women and children have received very good attention at the international, national and local levels. The policies contained in the International Convention on the Protection of Women, Children, and the State of Indonesia have also been ratified. Central government policies through the Ministry of Women's Empowerment and Child Protection in Child-friendly Districts/Cities as stated in the Indonesian Minister of Women's Empowerment and Child Protection. But in fact until now the trafficking of women and children (Human Trafficking) is still very high. The focus of this article is on how human trafficking is and its factors from the perspective of criminal law and human rights. This type of article is qualitative, which is analyzed with a normative approach. The results of the analysis show that the government's commitment as an effort to protect and respect the rights of women and children so as not to become victims of human trafficking is sufficient, but there are still factors so that trafficking in women and children is still happening. The problem of trafficking in women and children for whatever reason and purpose is still a form of violation of human rights. Keywords : Human Trafficking, Women, Children, Criminal, Human Rights